Antiscattering X-ray fluorescence analysis for large-area samples. Issue 11 (25th September 2019) - Zhao, Wenyang; Hirano, Keiichi; Sakurai, Kenji
Abstract : The scattering background in large-area X-ray fluorescence analysis (more than one square centimeter) has been greatly reduced by using highly polarized X-rays and by inserting a collimator plate between the sample and the detector. Abstract : Polarized X-rays have been utilized for many years to reduce the scattering background and optimize the signal-to-background ratio in the measurement of X-ray fluorescence spectra. It is vital to set a small solid angle in the direction of polarization for collecting fluorescence X-rays and scattering X-rays from a sample. Conventionally, this is realized by employing a large sample-to-detector distance and limiting the size of the probing area on the sample and the opening area of the detector. In this work, a collimator plate that assembles many parallel straight hollow capillaries is inserted between the sample and the detector. This can improve the signal-to-background ratio by tens of times when the primary X-rays have a high degree of polarization. The probing area on the sample is as large as 13.3 × 13.3 mm, making it convenient to survey trace elements dispersed in large-area environmental samples and industrial products. The sample-to-detector distance is as short as 3 mm, making the instrument compact and applicable to low- Z elements. The present polarization-collimator experimental scheme can exhibit its maximum potential in combination with strong and highly polarized synchrotron radiation with a reasonably large beam size.